Stewed Rhubarb Decoction Ameliorates Adenine-Induced Chronic Renal Failure in Mice by Regulating Gut Microbiota Dysbiosis - Wang, Rui; Hu, Baifei; Ye, Cheng; Zhang, Zhigang; Yin, Mingzhu; Cao, Qiushi; Ba, Yuanming; Liu, Hongtao (Frontiers in Pharmacology, 2022)
This study aimed to investigate the protective effect of Stewed Rhubarb (SR) decoction on chronic renal failure (CRF) through the regulation of gut microbiota. Using a CRF mouse model induced by a 0.2% adenine diet, we proved that SR decoction (2.0 g crude SR/kg) significantly reduced the levels of urea and creatinine in plasma of CRF mice, accompanied by the improvement of renal fibrosis and tubular atrophy, amelioration of inflammation, and inhibition of aquaporins damage. Also, SR decoction alleviated gut barrier damage, indicative of the elevated mRNA expression of intestinal mucins and tight junctions. By 16S rDNA sequencing, SR decoction reshaped the imbalanced gut microbiota in CRF mice by statistically reversing the abundance changes of a wide range of intestinal bacteria at family and genus levels, which further led to balance in the production of intestinal metabolites, including short-chain fatty acids (acetic acid, propionic acid, and valeric acid), indole, and bile acids (TUDCA and CDCA). Inversely, SR decoction failed to repress the occurrence of CRF in mice with gut microbiota depletion, confirming the essential role of gut microbiota in SR decoction-initiated protection against CRF. In summary, SR decoction can improve adenine-induced CRF in mice by remolding the structure of destructed gut microbiota community. Our findings shed light on the clinical application of SR decoction in nephropathy treatment.